PENGARUH SISTEM INFORMASI TERINTEGRASI TERHADAP KOMUNIKASI PERUSAHAAN - Nur Afiqah Nabila; Muhammad Irwan Padli Nasution (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This research aims to analyze the influence of integrated systems on communication within the company. Using qualitative descriptive methods, this research investigates how the implementation of an integrated system can increase the effectiveness of both internal and external communication, as well as identifying the impact of its implementation on communication within the company, including the effectiveness of internal communication, business process efficiency, and its effect on employee productivity. The research results show that an integrated system not only facilitates the flow of information, but also strengthens relationships between departments and with parties outside the company. In this modern era, with the rapid development of information technology, information systems have become an integral part of almost all aspects of life, including the business world. Companies around the world are increasingly relying on information technology to manage their operations, make better decisions, and remain competitive in an ever-changing business environment. Therefore, it is important to understand and analyze the impact of information systems on a company's operational efficiency. Integrated systems are now a crucial element in modern business processes.